The histone H3K36 demethylase Rph1/KDM4 regulates the expression of the photoreactivation gene PHR1 - Liang, Chung-Yi (Oxford University Press, 2011)
The dynamics of histone methylation have emerged as an important issue since the identification of histone demethylases. We studied the regulatory function of Rph1/KDM4 (lysine demethylase), a histone H3K36 demethylase, on transcription in Saccharomyces cerevisiae. Overexpression of Rph1 reduced the expression of PHR1 and increased UV sensitivity. The catalytically deficient mutant (H235A) of Rph1 diminished the repressive transcriptional effect on PHR1 expression, which indicates that histone demethylase activity contributes to transcriptional repression. Chromatin immunoprecipitation analysis demonstrated that Rph1 was associated at the upstream repression sequence of PHR1 through zinc-finger domains and was dissociated after UV irradiation. Notably, overexpression of Rph1 and H3K36A mutant reduced histone acetylation at the URS, which implies a crosstalk between histone demethylation and acetylation at the PHR1 promoter. In addition, the crucial checkpoint protein Rad53 acted as an upstream regulator of Rph1 and dominated the phosphorylation of Rph1 that was required for efficient PHR1 expression and the dissociation of Rph1. The release of Rph1 from chromatin also required the phosphorylation at S652. Our study demonstrates that the histone demethylase Rph1 is associated with a specific chromatin locus and modulates histone modifications to repress a DNA damage responsive gene under control of damage checkpoint signaling.